Selfless intervention exercising jurisdiction in the common interest - Ryngaert, Cedric (Oxford University Press, 2020)
Should states intervene in situations outside of their own territory in order to safeguard or promote the common good? In this book, Cedric Ryngaert addresses this key question, looking at how the international law of state jurisdiction can be harnessed to serve interests common to the international community. The author inquires how the purpose of the law of jurisdiction may shift from protecting national interests to furthering international concerns, such as those relating to the global environment and human rights. Such a shift is enabled by the instability of the notion of jurisdiction, as well as the interpretative ambiguity of the related notions of sovereignty and territoriality. There is no denying that, in the real world, 'selfless intervention' by states tends to combine with more insular considerations. This book argues, however, that such considerations do not necessarily detract from the legitimacy of unilateralism, but may precisely serve to trigger the exercise of jurisdiction in the common interest.